Numerical analysis of the influence of crack surface roughness on the crack path - Weber, Wilhelm; Willner, Kai; Kuhn, Günther (Engineering Fracture Mechanics, 2010)
The influence of the 3D frictional crack surface interaction on the fracture mechanical parameters as well as on the crack path is numerically investigated. For the solution of the boundary value problem the 3D dual boundary element method in terms of the discontinuous formulation is utilized. This method is especially suited for contact problems because it directly deals with the discontinuities at the crack surfaces. The contact problem is solved by the application of the penalty method. Coulomb's frictional law is utilized for the consideration of the dissipative nature of friction. For discrete steps within one load cycle the stress intensity factors are determined by an extrapolation procedure from the stress field. Based on the analysis of a load cycle, the cyclic stress intensity factors are obtained. For the simulation of crack propagation an implicit time integration scheme of a crack propagation law implemented in terms of a predictor-corrector scheme is applied. The influence of the crack surface roughness on the crack path is shown by numerical examples. © 2010 Elsevier Ltd.
UnivIS-Import:2015-03-09:Pub.2010.tech.FT.FT-TM.numeri
Keywords: 3D simulation; Crack surface interaction; Fatigue crack propagation